BA 206 - Principles of Management - Mindy Bean (Linn-Benton Community College, 2018)
The key decision-making role of managers in modern organizations. Includes the study of organizations, management styles, and selected administrative problems. An overview of the processes involved in managing a business, including business planning, organizing, controlling, staffing and leading. Covers various theories of management with emphasis on managing a business in the local, national or international marketplace.